Menurunkan Perilaku ADHD dengan Melakukan Aktivitas Fisik pada Anak Usia Dini - Chanet, Geraisa Dayura; Utami, Adnani Budi (Ridwan Institute, 2021)
The purpose of the study was to observe how to decrease ADHD reduction by doing physical activity in early childhood. The method in this study uses qualitative research design with single case experiement with intervention, namely physical activity such as swimming or karate and mentoring and counseling to parents and teachers. The intervention was carried out in swimming pools and subject schools for two weeks. Results obtained for two weeks, the subject can minimize difficult behavior focus, sitting still in class. Based on assessments conducted by observation method, interviews and psychological tests found that the subject had attention-attention-hyperactivity disorder (GPPH) or currently known as ADHD (attention deficit and hyperactivity disorder). The main feature of ADHD according to DSM V is that it often fails to pay attention, is careless, does not focus on when spoken to, often does not follow instructions in school, often leaves the seat while at school, cannot wait for the turn, always move and talk too much.